Effect of calcium chloride concentration on improving the quality of restructurized strawberry fruit (Fragaria x ananassa) - Lestario, Lydia Ninan; Herlia, Laurentsia Tabitha; Raharjo, Monika (Department of Agricultural Products Technology, Mulawarman University, 2026)
Strawberry is a very popular fruit due to their bright red color and aroma. sweet and slightly sour taste and nutritional value, especially vitamin C. Strawberries also contain anthocyanins, a reddish-purple pigment with high antioxidant activity. Nevertheless, they have a relatively short shelf life and are easily damaged because of their soft texture. They are usually processed into jam and other products that use high temperatures, which can damage nutritional compounds, including anthocyanins. Restructuring is an alternative method that can be used to extend the shelf life of strawberries without heat, thereby avoiding damage to the nutritional value and antioxidant activity. This study aimed to determine the effect of various Alginate and CaCl₂ concentrations (0, 0.1, 0.2, 0.3, 0.4, and 0.5%) on the quality of restructurized strawberries. The anthocyanin content was determined using the pH differential method; the texture was determined using a simple test to distinguish differences between treatments; the organoleptic test used hedonic methods with 30 panelists; and the shelf life tests were used to keep the real product until the quality decreased. Preliminary experiments showed that 2% alginate was optimal. The second step showed that 0.4% CaCl₂ was optimal.